COMMUNICATION AND RELIGIOUS MODERATION IN THE DEVELOPMENT OF BILEBANTE GREEN TOURISM VILLAGE, PRINGGARATA DISTRICT, CENTRAL LOMBOK REGENCY - Zaini, Ahmad Nasril (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This study aims to analyze and explain how religious communication and moderation in supporting the Development of Bilebante Green Tourism Village, Pringgarata District, Central Lombok Regency and to identify and analyze what are the challenges faced in maintaining religious harmony and moderation in Bilebante Green Tourism Village, Pringgarata District, Central Lombok Regency. The research methodology used in this study is qualitative research with a case study type. To obtain the results and objectives of the research, data collection procedures used in the field are observed, interviews, and documentation. The results of this study show that communication and religious moderation in supporting the development of the Bilebante green tourism village, that the values of religious moderation have been implemented in the life of the Bilebante people through four main indicators; commitment to nationality, tolerance, non-violence, and friendliness to local culture. The challenges in maintaining religious harmony and moderation in the Bilebante green tourism village include internal challenges that occur in the community, such as differences in perceptions, prejudices between residents, and different cultural backgrounds. Therefore, inclusive and participatory communication is the key to maintaining the harmony and sustainability of green tourism villages and religious moderation.